EXPLOITATION AND CPUE TREND OF THE SMALL PELAGIC FISHERIES IN THE SULAWESI SEA, INDONESIA - Lilis Sadiyah; Purwanto Purwanto; Andhika P. Prasetyo (Research Center for Fisheries, 2012)
One of the expected benefits of the Sulu-Celebes Sea Project during its implementation is to have increased fish stocks at demonstration sites, as indicated by the Catch per Unit of Effort (CPUE). Analysis of catch and effort data of the small pelagic fisheries by using the surplus yield model was done to obtain information on the likely trend of CPUE for the last ten years. By using the pajeko as the standardized fishing gear the trend of CPUE has been calculated. Between 2000-2005, the trend of production (catch), effort and CPUE followed the general pattern of the exploited fisheries that already fully exploited, where the increasing trend of effort was not followed by the increasing catch. On the other hand, the trend of CPUE is decreased. In the following years, the trend of both catch and CPUE do not follow the general pattern of the exploited fisheries. The trend of catch, effort and CPUE has likely been stable, indicating that the fishery in this period has been leveled-off. The status of exploitation of the small pelagic fish resources in the Indonesian Sulawesi Sea is demermined by the MSY level that has likely been surpassed during the period 2003-2004. Therefore with the increasing effort in the following year the trend of catch was relatively stable. It is likely that the small pelagic fish stock in the Indonesian Sulawesi Sea might be ‘fully exploited’.